(untitled) (ALPHA. Journal of Arts, Literature and Philosophy, 2017)
In this work we propose an elaboration of one of the lectures of Kant by Deleuze. Specifically, we consider the one that investigates the genesis of the trascendental. For that, we focus on the issue of the “being of the sensible”, and then relate it with the problem of genesis of the faculties. And for this, we expose a dialogue between some passages of Difference and repetition and the text The Idea of Genesis in Kant’s Esthetics. Finally, we search in the question about arts in Kant, read by Deleuze, a hint of what would mean to think on the sensible